A THE EFFECT OF PHYSICAL FITNESS EXERCISE ON GROSS MOTOR SKILLS OF CHILDREN AGED 5-6 YEARS AT DARMAWANITA KINDERGARTEN IN JANTHO CITY - Ramli, Selvia; Faridy, Faizatul; Juwita, Rani Puspa (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
Exercises aimed at improving physical fitness are crucial for kids' gross motor skill development. The gross motor movements of children aged 5 to 6 were found to be relatively low based on observations made at the Darma Wanita Kindergarten in Jantho City. This was due to the children's inability to practice body movements that connect large muscles to themselves or to train gross motor skills. The purpose of this study is to determine the impact of physical fitness activities on the gross motor skills of children enrolled in the Darma Wanita Kindergarten in Jantho City who are between the ages of five and six. "Quasi-experimental with a pretest-posttest control group design" is the type of experimental design research methodology used in this study, which is quantitative in nature. 35 children from classes B1 and B2 made up the population. In this study, two classes were used: class B2 served as the experimental class and class B1 served as the control class. In this study, the methods of observation and documentation were employed for data collection. The T test and the normalcy test were then used for data analysis. The data analysis results in this study demonstrate that the students' scores on the three developed indicators differed before and after treatment. The results of the pre- and post-tests indicate, based on computations using the t test and the normality test, that physical fitness exercise activities have an impact on the development of the gross motor skills of children in the Darma Wanita Kindergarten in Jantho City who are between the ages of five and six. When children aged 5 to 6 receive training in physical fitness exercises, their gross motor movements at Darma Wanita Kindergarten in Jantho City improve more significantly.